Surface chemistry of cellulose nanocrystals - Sirbu, Elena (2016)
Chemical surface modification of cellulose nanocrystals has had a fast development and increased interest from the scientific community as cellulose is the most abundantly available renewable polymer with many advantages such as nanoscale dimensions, high specific strength and modulus, high surface area, unique optical properties and the extraordinary modification potential to increase the application field. This thesis is aimed at expanding and improving upon the current knowledge in order to unlock new applications. Four esterification techniques were applied to the formation of cellulose nanocrystal esters of acrylic acid and methacrylic acid. The degree of surface substitution reached two to three surface hydroxyl groups (the maximum number) available for functionalization and this degree of substitution is very much dependent on the chosen esterification methodology. Two new fluorescently modified cellulose esters based on carbazole-9-yl-acetic acid and coumarin-3-carboxylic acid were synthesised using p-toluenesulfonyl chloride/pyridine and carbodiimide esterifications methods. Absorption and fluorescent properties were also measured and showed fluorescence proportional to the extent of surface functionalization. The maximum theoretically attainable degree of substitution could be reached while still maintaining the crystal structure of cellulose. Cationic cellulose nanocrystals were produced with a high positive surface charge when compared with the literature. The synthesis procedure was attempted in two steps and in a single step. The degree of modification for pyridinium acetate cellulose and methyl imidazolium acetate cellulose was found to depend significantly on the selected pathway. The cationic nature of the modifications was verified using zeta potential measurements and through adsorption of an anion dye. Synthesised cellulose acrylates and methacrylates were used in Thiol-Ene click reactions in which very mild and environmentally friendly reaction conditions proved to work from 10 min reaction times. Four different thiols were added, with and without hexylamine catalyst. In addition, an amidine functionalised cellulose nanocrystal was synthesised based on previously click-modified cellulose in a 2-hour reaction. Furthermore, the switchable behaviour of the synthesised nanoparticles was demonstrated by reverse bubbling with CO2 and Ar.